WOMEN EMPOWERMENT THROUGH MUSHROOM CULTIVATION AND PROCESSING IN ACEH UTARA - Rd. Selvy Handayani; Ismadi; Khaidir; Dewi Sartika Aryani; Zurrahmi Wirda; Usnawiyah (LPPM dan PM Universitas Samudra, 2022)
Training in mushroom cultivation has been chosen to be conducted in this community empowerment program, as we believe that this training can support the community in Desa Mesjid, Syamtalira Aron District Aceh Utara, not only to increase their income, but also can enrich their knowledge in serving healthier diets for their family. The main objective of this program was to increase community income and to enrich the knowledge about healthy foods by teaching them how to cultivate oyster mushroom. The results showed that the community was enthusiastic and satisfied with knowledge they obtained from the training. Ninety percent of them said it was a great, informative and useful activity. There is an increase in their knowledge about mushroom cultivation from 23% to 78%, and also how to process the mushroom into crispy fried mushroom and mushroom nugget and then to market them from 23% to 73%.